Intraduodenal conjugated bile salts exert negative feedback control on gall bladder emptying in the fasting state without affecting cholecystokinin release or antroduodenal motility. Issue 5 (1st May 2002) - van Ooteghem, N A M; Moschetta, A; Rehfeld, J F; Samsom, M; van Erpecum, K J; van Berge-Henegouwen, G P
Abstract : Background: Intraduodenal bile salts exert negative feedback control on postprandial gall bladder emptying. Aims: We wished to examine whether a similar control mechanism occurs in the fasting state. Methods: Intraduodenal bile salt depletion was achieved by 12 g of cholestyramine. Thereafter, in study A (seven subjects), the effects on gall bladder volume (by ultrasound) and antroduodenal motility of intraduodenal infusions of taurocholate egg yolk-phosphatidylcholine micelles were assessed. In study B (nine subjects), the effects on gall bladder volume of infusing mixed micelles composed of taurocholate (100 mM) and low (26 mM) or high (68 mM) amounts of egg yolk-phosphatidylcholine, or low amounts of dipalmitoylphosphatidylcholine were determined. Results: Cholestyramine induced strong and prolonged gall bladder contraction without cholecystokinin release. In study A, micellar infusions increased gall bladder volume without affecting migrating motor complex cycle length. In study B, intraduodenal infusion induced strong increases in gall bladder volume in the case of taurocholate micelles containing low amounts of egg yolk-phosphatidylcholine, moderate increases in micelles containing low amounts of dipalmitoylphosphatidylcholine but no change in micelles containing high amounts of egg yolk-phosphatidylcholine, in all cases without altered plasma cholecystokinin levels. Phosphatidylcholine hydrolysis was significantly higher after infusion of egg yolk-phosphatidylcholine compared with infusion of dipalmitoylphosphatidylcholine containing micelles. Intermixed micellar-vesicular bile salt concentrations (responsible for detergent effects) were higher in egg yolk-phosphatidylcholine than in dipalmitoylphosphatidylcholine containing model biles and if lyso-phosphatidylcholine was included. Conclusions: Intraduodenal bile salts exert negative feedback on fasting gall bladder volume. The modulating effects of various phospholipids may relate to their effects on intermixed micellar-vesicular bile salt concentrations.